Functional responses of Neoseiulus idaeus and Iphiseius degenerans (Acarina: Phytoseiidae) feeding on the cassava green mite, Mononychellus tanajoa (Acarina: Tetranychidae) - Akpokodje, G.; Odebiyi, J.; Ochieng, R.; Herren, H. (1990)
The functional responses of larva and female Iphiseius degenerans BERLESE and protonymph and female Neoseiulus idaeus (DENMARK & MUMA) were determined with different developmental stages of the cassava green mite (CGM), Mononychellus tanajoa BONDAR, as food supplied at densities of 1, 2, 5, 10, 20, 30, 40, and 50 individuals per 3,14cm² cassava leaf disc arena. All functional responses obtained were of the Holling's Type II curve with the highest plateaux when adult females of both N.idaeus and I. degenerans were preying on CGM eggs. Mean highest number of 14.3 CGM eggs/5-hours consumed by a female N. idaeus was not significantly different from the 13.0CGM eggs/5-hours of I. degenerans. There was a significant non-linear positive correlation between predator's search rate and prey density in all treatments. Larvae of I. degenrans displayed a unique search rate curve apparently associated with its non-obligatory predatory nature.